(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Hydronephrosis is one of the most commonly detected anomalies on pediatric abdominal ultrasound, yet data on its structural severity and laterality patterns in Bangladeshi children remain limited. Early and accurate sonographic characterization is essential for guiding referral, preventing complications, and avoiding unnecessary surgery. Objective: To evaluate the sonographic patterns of hydronephrosis in children presenting to a tertiary care hospital in Bangladesh, including grade of severity, laterality, and associated urinary tract findings. Methods: A prospective cohort study was conducted at Bangladesh Medical University (BMU), Dhaka, Bangladesh, from January 2024 to December 2025. A total of 143 children with suspected hydronephrosis underwent standardized renal ultrasound by a single trained pediatric radiologist. Hydronephrosis was graded using the Society for Fetal Urology (SFU) classification system (grades 0–4). Data were analyzed using SPSS version 23.0. Descriptive statistics were reported as frequencies and percentages. Results: Among 143 children (median age 4.8 years), hydronephrosis was unilateral in 57.3% (left-sided 58.5%) and bilateral in 42.7%. SFU grade 2 was most frequent (36.4%), followed by grade 3 (28.0%). High-grade hydronephrosis (grades 3–4) occurred in 37.8% of children. Mean anteroposterior pelvic diameter was 12.4±5.6 mm, increasing significantly with higher grade. Cortical thinning (21.7%) and ureteric dilatation (18.9%) were more common in high-grade disease (p<0.001). Conclusion: Moderate hydronephrosis (SFU grade 2) predominates in this cohort. High-grade hydronephrosis affects over one-third of children, supporting routine ultrasound screening and timely urology referral to prevent long-term renal morbidity. Journal of Paediatric Surgeons of Bangladesh (2025) Vol. 16 (1 & 2): 15-20